2022
DOI: 10.3390/atmos13071061
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen-Year Monitoring of Particulate Matter Exposure in the Parisian Subway: Data Inventory and Compilation in a Database

Abstract: The regularly reported associations between particulate matter (PM) exposure, and morbidity and mortality due to respiratory, cardiovascular, cancer, and metabolic diseases have led to the reduction in recommended outdoor PM10 and PM2.5 exposure limits. However, indoor PM10 and PM2.5 concentrations in subway systems in many cities are often higher than outdoor concentrations. The effects of these exposures on subway workers and passengers are not well known, mainly because of the challenges in exposure assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In this study, we focused on PM 10 exposure in the subway network, for which we had the largest amount of measurement data available (n = 18,148). These data were centralized in the quantitative database resulting from an exhaustive inventory of PM measurement campaigns and exposure monitoring programs that have been conducted in the company [57]. The quantitative results were abstracted as daily, monthly, or annual average values (in µg/m 3 ) along with contextual data abstracted in 30 variables (e.g., the measurement date, the measurement duration and method, the job, and the workplace location).…”
Section: Exposure Considered and Measurement Data Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focused on PM 10 exposure in the subway network, for which we had the largest amount of measurement data available (n = 18,148). These data were centralized in the quantitative database resulting from an exhaustive inventory of PM measurement campaigns and exposure monitoring programs that have been conducted in the company [57]. The quantitative results were abstracted as daily, monthly, or annual average values (in µg/m 3 ) along with contextual data abstracted in 30 variables (e.g., the measurement date, the measurement duration and method, the job, and the workplace location).…”
Section: Exposure Considered and Measurement Data Usedmentioning
confidence: 99%
“…The principle of JEM construction involves the definition of homogenous exposure groups (i.e., groups that combine workers with similar exposure level because of tasks or similar work conditions). From the previous studies, we identified that PM concentrations vary depending on the calendar period, line, and geographic sector of the subway network [15,36,57]. Therefore, adding these determinants as additional dimensions to define homogeneous exposure groups in the JEM was important.…”
Section: Jem Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the subway particles are coarser and have a very different chemical composition (Loxham and Nieuwenhuijsen 2019 ; Seaton et al 2005 ). PM sampled from underground transportation systems consists mainly of transition metals (Fe, Cu, Al, and Mn) (Ben Rayana et al 2022 ; Canu et al 2021a ; Loxham and Nieuwenhuijsen 2019 ) with a lower content of organic compounds compared to ambient PM. These differences relate to the type of emission sources, with abrasion/mechanical wear being important in subway environments, whereas secondary aerosols and combustion emissions being the major ambient PM source (COMEAP 2018a ).…”
Section: Introductionmentioning
confidence: 99%